Safety of perioperative prophylactic anticoagulation in laparoscopic nephron-sparing surgery - Zhong Wenwen, Ye Lei, Qiu Wenfeng, Wang Dejuan, Qiu Jianguang (Xin yixue, 2022)
Objective To analyze the safety of perioperative prophylactic anticoagulant therapy in patients undergoing laparoscopic nephron-sparing surgery. Methods Clinical data of 84 cases underwent laparoscopic nephron-sparing surgery were retrospectively analyzed. The baseline data, intraoperative blood loss, intraoperative blood transfusion rate, postoperative rebleeding rate, postoperative hemoglobin reduction value, and postoperative length of hospital stay were recorded. These parameters were statistically compared between patients treated with perioperative prophylactic anticoagulant therapy （medicine group, n = 50） and without perioperative prophylactic anticoagulant therapy （non-medicine group, n = 34）. Results There was no significant difference in intraoperative blood loss （50.0 （30.0,100.0）mL vs.50.0 （45.0,100.0）mL）, intraoperative blood transfusion rate （0 vs.2.9%）, postoperative rebleeding rate （4.0% vs.2.9%）, postoperative hemoglobin reduction value （14.0（8.0,23.0） g/L vs.17.7（9.3,28.5） g/L）, and postoperative length of hospital stay （6.0（5.0,7.0）d vs.7.0（4.0,9.3）d）between the medicine and non-medicine groups （all P > 0.05）. Conclusion Perioperative prophylactic anticoagulation is safe and feasible for patients undergoing laparoscopic nephron-sparing surgery.